(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Pedagogists and psychologists emphasize that it is important to develop students’ thinking and analytical abilities. The basis of these abilities is reflection.This article talks about the formation of reflexive skills in elementary school students based on game-educational technology.